ANALISIS KEBUTUHAN DALAM PENGEMBANGAN MODUL PADA MATA PELAJARAN DASAR-DASAR KONSTRUKSI BANGUNAN - Kayla Azahra (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
Providing learning modules that are in line with developments in information and technology in the basics of building construction is a current need that has been studied a lot through research. This research aims to determine the need for developing modules on the basics of building construction subject through descriptive qualitative research methods with a literature study approach chosen according to the urgency of the existing case. The data sources are in the form of previous research, journals and books which were selected based on the relevance of the material, namely the need for developing modules in learning and teaching activities on the basics of building construction. The results of the research based on the selected data show that the need for developing modules in the basics of building construction subject is that the appearance and content of the material are arranged attractively, the learning material is structured concisely and is easy to understand, and the media used is interactive learning media that can involve students. directly